23Na MRI depicts early changes in ion homeostasis in skeletal muscle tissue of patients with duchenne muscular dystrophy. Issue 4 (4th February 2019) - Gerhalter, Teresa; Gast, Lena V.; Marty, Benjamin; Martin, Jan; Trollmann, Regina; Schüssler, Stephanie; Roemer, Frank; Laun, Frederik B.; Uder, Michael; Schröder, Rolf; Carlier, Pierre G.; Nagel, Armin M.
Abstract : Background: Duchenne muscular dystrophy (DMD) is a hereditary neuromuscular disease leading to progressive muscle wasting. Since there is a need for MRI variables that serve as early sensitive indicators of response to treatment, several quantitative MRI methods have been suggested for disease monitoring. Purpose: To evaluate the potential of sodium ( 23 Na) and proton ( 1 H) MRI methods to assess early pathological changes in skeletal muscle of DMD. Study Type: Prospective clinical study. Population: 23 Na and 1 H MRI of the right leg were performed in 13 patients with DMD (age 7.8 ± 2.4) and 14 healthy boys (age 9.5 ± 2.2). Field Strength/Sequence: 3 T including a multiecho‐spin‐echo sequence, diffusion‐weighted sequences, 1 H spectroscopy, 3‐pt Dixon, and 23 Na ultrashort echo time sequences. Assessment: We obtained water T2 maps, fat fraction (FF), pH, and diffusion properties of the skeletal muscle tissue. Moreover, total tissue sodium concentration (TSC) was calculated from the 23 Na sequence. Intracellular‐weighted 23 Na signal (ICwS) was derived from 23 Na inversion‐recovery imaging. Statistical Tests: Results from DMD patients and controls were compared using Wilcoxon rank‐sum tests and repeated analysis of variance (ANOVA). Spearman‐rank correlations and area under the curve (AUC) were calculated to assess the performance of the different MRI methods to distinguish dystrophic from healthy muscle tissue. Results: FF, water T2, and pH were higher in DMD patients (0.07 ± 0.03, 39.4 ± 0.8 msec, 7.06 ± 0.03, all P  < 0.05) than in controls (0.02 ± 0.01, 36.0 ± 0.4 msec, 7.03 ± 0.02). No difference was observed in diffusion properties. TSC (26.0 ± 1.3 mM, P  < 0.05) and ICwS (0.69 ± 0.05 a.u., P  < 0.05) were elevated in DMD (controls: 16.5 ± 1.3 mM and 0.47 ± 0.04 a.u.). The ICwS was frequently abnormal in DMD even when water T2, FF, and pH were in the normal range. 23 Na MRI showed higher AUC values in comparison to the 1 H methods. Data Conclusion: Sodium anomalies were regularly observed in patients with DMD compared with controls, and were present even in absence of fatty degenerative changes and water T2 increases. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;50:1103–1113.